Improving the Competency of Junior High School Teachers Through Training and Mentoring in STEM-Based PBL Model - Shamdas, Gamar BN; Bialangi, Mursito; Fardha, Rizka; Jamhari, Mohammad (Universitas Lambung Mangkurat, 2025)
A deficit in teachers' skills and knowledge in designing innovative technology-based learning can impact student learning outcomes. This community service aims to provide training on designing learning using the STEM-based PBL model for teachers at SMP Negeri 18 Palu, Central Sulawesi. This program involved 40 SMP Negeri 18 Palu teachers and was conducted in July 2024. Utilizing a participatory action research approach, this program included material presentations, interactive discussions, and assignments assessed through questionnaires, observation sheets, and assignment sheets. The questionnaires were distributed before training activities, observation sheets were used during training and mentoring activities, and assignment sheets were distributed immediately after the discussion ended. The outcomes of the questionnaire showed that 100% of teachers analyzed learning outcomes and learning objectives before designing the lesson, 90% of teachers were familiar with PBL, 45% of teachers had designed learning using the PBL and implemented it, 10% of teachers had mastered PBL syntax and 100% of teachers had never designed learning with a STEM and combining it with PBL. The observation results were that 100% of teachers in each group played an active role, helped each other and worked together to complete assignments, established good communication with fellow teachers in their groups, and had a high level of responsibility in completing their group assignments. The assignment results show that 100% of teachers succeeded in designing learning using the PBL learning model and integrating it with a STEM approach. This community service’s success suggests a continued need for similar training efforts in designing STEM-based PBL models. Expanding workshops to facilitate the implementation of STEM-integrated PBL models in learning is also necessary.Top of Form